Parallel Imports of Pharmaceuticals Evidence from Scandinavia and Policy Proposals for Switzerland - Poget, Cédric Julien (Birkhäuser Basel : Imprint: Birkhäuser, 2008)
Parallel trade occurs if international price differences for identical products are high and a policy of regional or international exhaustion of the respective property right has been implemented in the high price country. The work by C. Poget analyses how parallel imports of pharmaceuticals are affecting end consumer prices and drug expenditures in three Scandinavian countries, Sweden, Denmark and Norway. Based on his observations he derives proposals for policy reforms in EU member countries and Switzerland.